Macroevolutionary consequences of mast seeding. (6th December 2021) - Dale, Esther E.; Foest, Jessie J.; Hacket-Pain, Andrew; Bogdziewicz, Michał; Tanentzap, Andrew J.
Abstract : Masting characterizes large, intermittent and highly synchronous seeding events among individual plants and is found throughout the plant Tree of Life (ToL). Although masting can increase plant fitness, little is known about whether it results in evolutionary changes across entire clades, such as by promoting speciation or enhanced trait selection. Here, we tested if masting has macroevolutionary consequences by combining the largest existing dataset of population-level reproductive time series and time-calibrated phylogenetic tree of vascular plants. We found that the coefficient of variation (CV p ) of reproductive output for 307 species covaried with evolutionary history, and more so within clades than expected by random. Speciation rates estimated at the species level were highest at intermediate values of CV p and regional-scale synchrony (S r ) in seed production, that is, there were unimodal correlations. There was no support for monotonic correlations between either CV p or S r and rates of speciation or seed size evolution. These results were robust to different sampling decisions, and we found little bias in our dataset compared with the wider plant ToL. While masting is often adaptive and encompasses a rich diversity of reproductive behaviours, we suggest it may have few consequences beyond the species level. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.